Review of the theoretical underpinnings in the creative tourism research field - Carvalho, Rui Miguel Ferreira; University of Aveiro, Phd student in tourism Member of the research unit on Competitiveness, Governance and Public Policies Tourism teacher at the Vocational School of Torres Novas (2019)
Despite the rising number of creative tourism publications, this field is still an emerging research area. Its studies range from urban cities to rural areas, including different uses of creativity, culture, events, creative networks and experience co-creation. This study focused on the main theoretical subjects of creative tourism as a separate field of research. The results pinpoint vital issues present in the creative tourism literature, while recognising that this field is still evolving. After a thorough literature review, three main theoretical streams of contributions were found in the literature: 1) creativity and its relationship to tourism, (2) specialised consumption as a characteristic of postmodern tourists and 3) the experience economy paradigm and experience co-creation. The findings include the main theoretical underpinnings of creative tourism that have caused this special interest tourism to attract so much attention in recent years.